Service Quality, Brand Image, and Patient Loyalty in Indonesian Primary Healthcare: Patient Satisfaction as a Mediator - Nurnaningtyas, Iqlima Seilena Rachma; Wijaya, Liliana Inggrit (Yayasan Sembilan Pemuda Indonesia, 2026)
This study investigates the effects of service quality and brand image on patient loyalty, with patient satisfaction as a mediating variable, at a public primary healthcare centre in Indonesia. Using a cross-sectional survey of 300 outpatients with at least two visits for different diagnoses, data were analyzed via Structural Equation Modeling (SEM) and the Sobel test, and model fit was evaluated with multiple indices. The results indicate that service quality (CR=6.54, p<0.001) and brand image (CR=5.94, p<0.001) significantly enhance patient satisfaction, whereas service quality (CR=0.59, p=0.56), brand image (CR=1.77, p=0.08), and patient satisfaction (CR=-0.01, p=0.99) do not significantly affect patient loyalty, and satisfaction does not mediate the relationships (Sobel p=0.995). The model exhibited poor fit (CFI=0.79, RMSEA=0.092), indicating that findings should be interpreted cautiously. The study contributes to understanding that satisfaction can be improved by service quality and institutional image, but loyalty may depend on other factors such as trust, access, and continuity of care. Health centre managers should not assume satisfaction alone ensures loyalty, and future research should test alternative mediators using longitudinal designs and better-fitting models.